Biomechanical simulation of bed turning post-acetabular fracture fixation - Haiyang Wu; Zaijie Sun; Qixiao Shen; Xuejian Wu; Cheng Li; Xianhua Cai (Scientific Reports)
Abstract Before patients begin out-of-bed exercises following internal fixation surgery for acetabular fractures, turning over in bed serves as a crucial intervention to mitigate complications associated with prolonged bed rest. However, data on the safety of this maneuver post-surgery are limited, and the biomechanical evidence remains unclear. This study aims to introduce a novel loading protocol designed to preliminarily simulate the action of turning over in bed and to compare the biomechanical properties of two fixation methods for acetabular fractures under this new protocol. A RNJ-500 microcomputer-controlled electronic torsion tester was utilized to simulate the action of turning over in bed and to conduct a dynamic torsion loading test. Initially, the torque values and torsional stiffness of six intact pelvis specimens (Group A) were measured. A double-column acetabular fracture model was then created and stabilized using two different fixation methods: the Dynamic Anterior Plate-Screw System for the Quadrilateral plate (DAPSQ, Group B) and the traditional anterior reconstruction titanium plate plus a 1/3 tubular buttress plate (Group C). All specimens underwent cyclic torsion loading ranging from 2° to 8°. The medial displacement and strain values of the quadrilateral plate were recorded and analyzed. As the torsion angles increased from 2° to 8°, Groups A and B exhibited significantly higher torque values compared to Group C (all P < 0.05). Group C demonstrated notably lower torsional stiffness (1.51 ± 0.20) relative to Group A (2.33 ± 0.25, P < 0.05) and Group B (2.21 ± 0.29, P < 0.05). Additionally, the medial displacement of the quadrilateral plate was significantly reduced in Group B compared to Group C at all measured time points (P < 0.05). And Group C exhibited significantly higher maximum tensile and compressive strain than Group B (all P < 0.05). The DAPSQ plate with quadrilateral screws provides superior anti-rotational stability in a double-column acetabular fracture model under the newly established torsion loading protocol.